On the threshold of the Holocaust : anti-Jewish riots and pogroms in occupied Europe ; Warsaw-Paris-The Hague-Amsterdam-Antwerp-Kaunas - Szarota, Tomasz 1940- (Geschichte - Erinnerung - Politik, 2015)
"In the early months of the German occupation during WWII, many of Europe's major cities witnessed anti-Jewish riots, anti-Semitic incidents, and even pogroms carried out by the local population. Who took part in these excesses, and what was their attitude towards the Germans? Were they guided or spontaneous? What part did the Germans play in these events and how did they manipulate them for their own benefit? Delving into the source material for Warsaw, Paris, The Hague, Amsterdam, Antwerp, and Kaunas, this study is the first to take a comparative look at these questions. Looking closely at events many would like to forget, the volume describes various characters and their stories, revealing some striking similarities and telling differences, while raising tantalising questions"--